2021
DOI: 10.3390/jof7060402
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhiza-Induced Resistance against Foliar Pathogens Is Uncoupled of Nutritional Effects under Different Light Intensities

Abstract: The use of microbial inoculants, particularly arbuscular mycorrhizal fungi, has great potential for sustainable crop management, which aims to reduce the use of chemical fertilizers and pesticides. However, one of the major challenges of their use in agriculture is the variability of the inoculation effects in the field, partly because of the varying environmental conditions. Light intensity and quality affect plant growth and defense, but little is known about their impacts on the benefits of mycorrhizal symb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 71 publications
1
20
0
1
Order By: Relevance
“…Knowledge of the adverse effects of agrochemicals on human health and the environment has led to the search for environmentally friendly methods to control plant diseases and pests. Beneficial soil microbes promoting plant defenses, such as non-pathogenic bacteria [ 56 ], mycorrhizal fungi [ 57 , 58 , 59 ], and plant-growth-promoting fungi [ 18 , 60 ], are a possible alternative to pesticides. Fungi belonging to the genus Trichoderma are known as plant growth promoters and control agents against plant pathogens [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the adverse effects of agrochemicals on human health and the environment has led to the search for environmentally friendly methods to control plant diseases and pests. Beneficial soil microbes promoting plant defenses, such as non-pathogenic bacteria [ 56 ], mycorrhizal fungi [ 57 , 58 , 59 ], and plant-growth-promoting fungi [ 18 , 60 ], are a possible alternative to pesticides. Fungi belonging to the genus Trichoderma are known as plant growth promoters and control agents against plant pathogens [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, fungi and yeast possess analogous beneficial bioactivities as plant growth-promoting rhizobacteria (PGPR) [8,[18][19][20][21][22]. Beneficial fungi are major players in natural and agricultural habitats and ecosystems, where they are involved in organic matter recycling, nutrient availability, and plant health and growth [23,24]. Many reports have demonstrated that arbuscular mycorrhizal fungi (AMF), alone or in combination with plant growth promoting rhizobacteria (PGPRs), such as Bacillus or Pseudomonas, increase nutrient availably for the host plant and promote its development and yield [19,23,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Mycorrhizal symbiosis provided an array of genotype-specific growth and defensive benefits to host plants, altering patterns of host growth and infection with a foliar fungal pathogen. Mycorrhizal fungi have been shown to protect agricultural plants against belowground (Azcón-Aguilar & Barea, 1996) and foliar (Fiorilli et al ., 2018, Pozo de la Hoz et al ., 2021) pathogens in controlled laboratory conditions, but this is the first evidence of mycorrhizal effects on pathogen dynamics in a genetically diverse wild host, and under natural ecological and epidemic conditions. In addition to benefits, we found that association with mycorrhizal fungi introduced occasional risks to host plants, as we observed an increased likelihood of infection in some host populations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, disease susceptibility and mycorrhizae-derived defense effects appeared to be linked in the host genotypes: more susceptible host genotypes (in the absence of the mutualists) received stronger protection against disease when inoculated with mycorrhizal fungi. Arbuscular mycorrhizal fungi have been shown to protect agricultural plants against belowground (Azcón-Aguilar & Barea, 1996) and foliar (Fiorilli et al ., 2018, Pozo de la Hoz et al ., 2021) pathogens in controlled laboratory conditions, but our results provide the first evidence of how microbial mutualists can shift patterns of host infection in genetically diverse wild populations under pathogen attack. Mycorrhizal fungi also appeared to be linked to a growth-defense trade-off in the hosts: mycorrhizal-inoculated plants grew larger and became more infected by the pathogen, with the host genotypes that obtained the greatest growth benefit from mycorrhizal fungi also suffering the largest increases in disease.…”
Section: Discussionmentioning
confidence: 99%